ANALISIS PENGOLAHAN LIMBAH CAIR ANALISIS PENGOLAHAN LIMBAH CAIR TERHADAP KUALITAS AIR DI PABRIK TEMPE MARINDAL 1 DUSUN 9 KECAMATAN PATUMBAK KABUPATEN DELI SERDANG TAHUN 2025 - Sitio, Sri Sudewi Pratiwi; Sembiring, Efrata - (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
Fermented Soybean is a traditional food made from fermented soybeans and it is widely favored by the Indonesian population. In 2018, Indonesia became one of the largest producers of processed soybeans, with production reaching 982.5 thousand tons. The popularity of soybean is supported by its affordability, making it accessible to all levels of society (Pakpahan et al., 2021). Industrial wastewater discharged directly into water bodies has become one of the main causes of environmental pollution, particularly water pollution. This study aimed to analysis the wastewater treatment system applied by the factory in reducing Biological Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) levels before being discharged into the environment. This study was experimental in nature, with laboratory analysis. Wastewater sampling was conducted using the composite sampling method. Samples were taken from two points: the raw wastewater (inlet) and treated wastewater from the drainage outlet (outlet). The results showed a decrease in BOD and COD levels before and after wastewater treatment at the Tempe Factory in Marindal 1, Hamlet 9, with BOD values of 91,000 and COD values of 56,000, and an Asymp. Sig (2-tailed) value of 0.000. Since the significance value was < 0.05, it was concluded that there was a significant reduction in BOD and COD levels. In conclusion, the wastewater treatment system at this tempe factory was able to reduce organic pollutant levels. It is recommended that the factory establish a wastewater treatment plant (WTP) to ensure that discharged wastewater is safe for the environment